TEACHER PERFORMANCE REVIEWED FROM PROFESSIONAL COMPETENCIES, INFRASTRUCTURE FACILITIES, MOTIVATION, AND WORK DISCIPLINE (Study on Education Staff at SMP Batik Surakarta) - Anita Dwi Ratnani; Istiatin Istiatin; Sarsono Sarsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to test and analyze professional competency variables, infrastructure, motivation, and work discipline on teacher performance at SMP Batik Surakarta. This research method uses a quantitative descriptive research design. The population is all teachers of SMP Batik Surakarta which amounts to 46 people. The sampling technique in this study is census technique or saturated sample as many as 46 people. Data retrieval using questionnaires and data analysis using SPSS 22.00 for multiple linear regression analysis calculations, F tests, t-tests, and determination coefficients. The results showed that professional competence, infrastructure, motivation, and work discipline affect teacher performance. Based on statistical tests obtained adjusted R square (R2) of 73.7% which showed that 73.7% changes in teacher performance variables were explained by variables of professional competence, infrastructure, motivation, and work discipline, while the remaining 26.3% were influenced by other variables that were not studied, such as leadership, employee satisfaction, and school culture.